Development of double-pulse lasers ablation system for generating gold ion source under applying an electric field. (December 2015) - Khalil, A.A.I.
Abstract: Double-pulse lasers ablation (DPLA) technique was developed to generate gold (Au) ion source and produce high current under applying an electric potential in an argon ambient gas environment. Two Q-switched Nd:YAG lasers operating at 1064 and 266 nm wavelengths are combined in an unconventional orthogonal (crossed-beam) double-pulse configuration with 45° angle to focus on a gold target along with a spectrometer for spectral analysis of gold plasma. The properties of gold plasma produced under double-pulse lasers excitation were studied. The velocity distribution function (VDF) of the emitted plasma was studied using a dedicated Faraday-cup ion probe (FCIP) under argon gas discharge. The experimental parameters were optimized to attain the best signal to noise (S/N) ratio. The results depicted that the VDF and current signals depend on the discharge applied voltage, laser intensity, laser wavelength and ambient argon gas pressure. A seven-fold increases in the current signal by increasing the discharge applied voltage and ion velocity under applying double-pulse lasers field. The plasma parameters (electron temperature and density) were also studied and their dependence on the delay (times between the excitation laser pulse and the opening of camera shutter) was investigated as well. This study could provide significant reference data for the optimization and design of DPLA systems engaged in laser induced plasma deposition thin films and facing components diagnostics. Highlights: Production of Au ion sources by DP-Lasers technique. DP-Lasers techniqueis superior as compared to the SP-laser. This work is a great benefit for optimizations of many experiments.